PENGARUH KONSENTRASI DAN LAMA PERENDAMAN EKSTRAK DAUN SIRSAK (Annona muricata Linn) TERHADAP KETEBALAN KERABANG DAN PENYUSUTAN BERAT TELUR ITIK - Mey Anggraeni Tamal (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
This study aims to determine the effect of time immersion with soursop leaf extract and storage time to the quality of duck eggs namely the thickness of the shell and the shrinkage of the egg weight. The study design was complete randomized design (RAL) factorial pattern with 2 treatment factors ie first factor: soaking for 20 hours and immersion for 40 hours and second factor: level of soursop leaf extract 2% and 4% during storage 0, 7, 14, 21 , 28, 35 and 42 days at room temperature with 3 replications. The result of the analysis based on anova spss analysis known that 28 days storage of different thickness of the shell is very real (P <0.01) at soaking 20 hours and 40 hours while the interaction between soaking and soursop leaf extract concentration is not significantly different as well as 35 days storage there is a significant difference in long soaking (P <0.05) while interaction between soaking time and soursop leaf extract level was also significantly different (P <0.05), while soursop extract level of 2% and 4% was not significantly different (P˃0.05). On shrinkage of egg weight, yield of soaking time significantly different to the shrinkage of egg storage weight 0 days (P <0.05). The shrinking weight of 28 days storage eggs was significantly different at the level of soursop leaf extract of 2% and 4% (P <0.05) while the interaction between soaking and soursop leaf extract was very significantly P <0.01.